Effect of Sacroiliac Joint Mobilization on Chronic Non-Spacific Low Lumbar Pain and Function in Women - Justinas Jarulaitis; Pavelas Zachovajevas (Lithuanian Sports University, 2020)
Background. Research aim was to investigate the effect of sacroiliac joint mobilization on chronic non-specific lumbar pain and function in women. Methods. 1. VAS scale evaluation; 2. Measurement of lumbar range of motion; 3. Lumbar muscle stamina tests. Twenty women who felt chronic non-specific lumbar pain and havd sacroiliac joint disfunction were investigated in this research. Results. The results of the study showed that the pain decreased from 3.87 ± 0.41 to 1.86 ± 0.33 points in the study group, and from 3.4 ± 0.52 to 1.6 ± 0.28 points in the control group (p < 0.05). The mean value of the abdominal muscle endurance test in the study group increased by 21.2 ± 3.65 s, in the control group - by 19.6 ± 3.69 s (p < 0.05). The isometric means of the abdominal muscle endurance test increased by 21.7 ± 2.58 s in the study group - and by 18.1 ± 4.07 s in the control group (p < 0.05). After physiotherapy, a statistically significant improvement in torso movement amplitudes was observed in both groups, but no statistically significant change was observed between the groups. Conclusions. Spinal stabilization exercises combined with sacroiliac joint mobilization were more effective treatment than the use of stabilization exercises alone, as they statistically significantly reduced the intensity of perceived pain and increased torso muscle endurance. Keywords: sacroiliac joint mobilization, chronic non-specific lumbar pain, functional lumbar indicators.